2015
DOI: 10.1177/2050640615618043
|View full text |Cite
|
Sign up to set email alerts
|

Rifabutin-based 10-day and 14-day triple therapy as a third-line and fourth-line regimen forHelicobacter pylorieradication: A pilot study

Abstract: Background and aim: This prospective randomized study was designed to assess the efficacy of 10-day and 14-day rifabutinbased triple therapy as a third-or fourth-line rescue therapy. Methods: Patients who failed first-and second-line eradication therapy were enrolled. H. pylori was isolated from gastric biopsy specimens and the rpoB mutation status, a factor of resistance to rifamycins, and minimum inhibitory concentrations (MICs) of rifabutin and amoxicillin were determined. Enrolled patients were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 27 publications
5
69
0
Order By: Relevance
“…2 We agree with them in terms of the importance of confirming tuberculosis status before starting rifabutin therapy, including the regimen, and the assurance of empirical rescue regimens especially in third-or fourth-line treatment.…”
supporting
confidence: 56%
“…2 We agree with them in terms of the importance of confirming tuberculosis status before starting rifabutin therapy, including the regimen, and the assurance of empirical rescue regimens especially in third-or fourth-line treatment.…”
supporting
confidence: 56%
“…QuantiFERON-TB Gold In-Tube test), since its use could imply the onset of antibiotic resistance, thus precluding its effectiveness against Koch's bacillus. Further, H. pylori resistance to rifabutin is low, as confirmed in the paper of Mori et al 1 Indeed, genotypic resistance revealed by mutations in the rpoB gene (a factor of resistance to rifamycins) has been found only in 3 out of 29 patients, despite phenotypic resistance to rifabutin being observed only in one patient at culture. This disagreement suggests that, at the moment, a valid genotypic marker for rifabutin resistance may not be available yet.…”
mentioning
confidence: 64%
“…8,9 In this regard, Mori et al showed that the 29% of patients in the 14-day and the 8.3% in the 10-day arm stopped the treatment due to adverse events. 1 In our experience, 10 Finally, the ideal combination of antibiotics with rifabutin should be guided by the previous treatment failures. This detail has not been reported by Mori et al, 1 even if they found that 16 strains (55%) were resistant to amoxicillin.…”
mentioning
confidence: 98%
See 2 more Smart Citations